Synbiotics for the Management of Cancer - Mishra, Neeraj; Bhatt, Shvetank; Paudel, Keshav Raj.; M Hansbro, Philip; Dua, Kamal (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book illustrates the significance of probiotics and prebiotics for the management of various types of cancers. The up-to-date chapters provide recent information about the effect of anticancer treatment approaches on gut microbiota, the correlation between ROS and synbiotics for effective cancer treatment, and the influence of synbiotics on inflammation and immune microenvironment for cancer treatment. It also describes the regulatory issues about synbiotics in the management of cancer. This book is an essential resource for scientists working in the field of cancer, pharmaceutical & clinical sciences, and cancer clinicians. This book is also very useful for undergraduate and postgraduate students of Pharmacy and Biotechnology and medical researchers, mainly working in microbiology, immunology, and cancer biology.
Chapter 1_Introduction to Cancer -- Chapter 2_Effect of anticancer treatment approches on gut microbiota -- Chapter 3_Synbiotic: A promising approach for the treatment of cancer -- Chapter 4_Correlation between ROS and Synbiotics for effective treatment of cancer -- Chapter 5_Influence of synbiotics on inflammation and immune microenvironment for the treatment of cancer -- Chapter 6_Synbiotics in colorectal cancer -- Chapter 7_Synbiotics in cervical cancer -- Chapter 8_Synbiotics in prostate cancer -- Chapter 9_Synbiotics in gastric cancer -- Chapter 10_Synbiotics in lung cancer -- Chapter 11_Synbiotics in small cell pancretatic cancer -- Chapter 12_Synbiotics in breast cancer -- Chapter 13_Synbiotics in hepatocellular carcinoma -- Chapter 14_Synbiotics in ovarian cancer -- Chapter 15_Regulatory issues of synbiotics in cancer.
Keywords: Pharmacology; Cancer; Cancer -- Treatment; Pharmacology; Cancers; Cancer Therapy